Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/1755-5922.12089
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Atrial Remodeling: Mechanisms and Potential Upstream Therapies

Abstract: Summary Atrial fibrillation (AF) is the most common cardiac arrhythmia in clinical practice, and its prevalence has increasing substantially over the last decades. Recent data suggest that there is an increased risk of AF among the patients with diabetes mellitus (DM). However, the potential molecular mechanisms regarding DM‐related AF and diabetic atrial remodeling are not fully understood. In this comprehensive review, we would like to summarize the potential relationship between diabetes and atrial remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 89 publications
0
33
0
1
Order By: Relevance
“…All of these metabolic changes lead to endothelial dysfunction, abnormal activation of the reninangiotensin-aldosterone system (RAAS) and acceleration of atherogenesis, which could be responsible for AF occurrence [2,[7][8][9]. Diabetes could also cause structural, electrical, electromechanical and autonomic remodelling [10].…”
Section: Mechanisms Of the Relationship Between Diabetes And Afmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these metabolic changes lead to endothelial dysfunction, abnormal activation of the reninangiotensin-aldosterone system (RAAS) and acceleration of atherogenesis, which could be responsible for AF occurrence [2,[7][8][9]. Diabetes could also cause structural, electrical, electromechanical and autonomic remodelling [10].…”
Section: Mechanisms Of the Relationship Between Diabetes And Afmentioning
confidence: 99%
“…Atrial fibrosis could be caused by inflammation (oxidative stress), increased production of advanced glycation end products, increased expression of transforming growth factor-␤ and expression changes of gap junction proteins [10].…”
Section: Atrial Structural Remodellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have demonstrated that TZDs prevent atrial electrical and structural remodeling through their antiinflammatory and antioxidant properties [75][76][77][78][79]. The possible targets of PPAR-c agonists include transforming growth factor-b (TGF-b), tumor necrosis factor-a (TNF-a), atrial natriuretic peptide (ANP), superoxide dismutase (SOD), malondialdehyde (MDA), NADPH oxidase subunits, and voltage-dependent Ca 2+ currents [80]. In the clinical setting, anecdotal evidence indicated a remarkable improvement of paroxysmal atrial fibrillation (AF) in 2 diabetic patients after treatment with rosiglitazone [81].…”
Section: Upstream Therapies For Diabetes Mellitus Related Atrial Remomentioning
confidence: 99%
“…Although the pathophysiological mechanisms linking diabetes mellitus (DM) to AF development have not been completely elucidated. Autonomic, electrical and structural remodeling involving activation of proinflammatory pathways, abnormalities of calcium (Ca 2+ ) homeostasis, as well as oxidative stress‐mediated damage play important roles 3, 4, 5, 6…”
mentioning
confidence: 99%